0
$\begingroup$

We have a equation: $2x^2+7x+3$
I tried to find the vertex of the parabola by this formula: $a(x-h)^2+k$
but I could not get it.
I got this: but it is not right.
$2(x^2+ \frac{7}{2}x+\frac{49}{4})+3-\frac{49}{2}$
What's the problem? Is it possible to solve it by completing square?

$\endgroup$
  • $\begingroup$ Why do you want to find the vertex by strictly completing the square ? $\endgroup$ – Rebellos Nov 24 '18 at 11:13
  • $\begingroup$ Because my book is given this formula. $\endgroup$ – Ehsan Zehtabchi Nov 24 '18 at 11:16
  • $\begingroup$ The formula makes no sense. You don't need a negative sign there. $\endgroup$ – Rebellos Nov 24 '18 at 11:18
3
$\begingroup$

Completing the square, it is :

$$2x^2 + 7x + 3 = 2\bigg(x^2+ \frac{7}{2}x + \frac{49}{16}\bigg) - \frac{25}{8} = 2\bigg(x + \frac{7}{4}\bigg)^2 - \frac{25}{8}$$

Thus, the vertex can be found at the point where the "completed square term" equals zero :

$$x+\frac{7}{4} = 0 \Leftrightarrow x = -\frac{7}{4}$$

This is truly the vertex point, as it can be cross-validated by the fact that a vertex of a parabola can be found at :

$$x_v = -\frac{b}{2a} \Rightarrow x_v = -\frac{7}{2\cdot 2}$$

Now, the other coordinate of the vertex is the remaining constant term on the right, thus $-25/8$.

This means that the given vertex coordinates, are :

$$(h,k) = \bigg(-\frac{7}{4},-\frac{25}{8}\bigg)$$

$\endgroup$
2
$\begingroup$

It's possible.

\begin{align*} 2x^2 + 7x + 3 & = 2\left(x^2 + \frac{7}{2} x \right) + 3 = 2\left(\left(x + \frac{7}{4}\right)^2 - \left(\frac{7}{4}\right)^2 \right) + 3 \\ & = 2 \left(x + \frac{7}{4}\right)^2 - \frac{49}{8} + 3 = 2 \left(x + \frac{7}{4}\right)^2 - \frac{25}{8} \end{align*} So we have the vertex at $(h,k) = \left(- \frac{7}{4}, - \frac{25}{8}\right)$.

$\endgroup$
2
$\begingroup$

In completing the square, you want to follow a plan like below.

$$ax^2+bx+c = 0$$

$$x^2+\frac{b}{a}x+\frac{c}{a} = 0 \implies x^2+\frac{b}{a}x = -\frac{c}{a}$$

You want to reach a quadratic trinomial on the LHS so you can solve it. This is done by adding $\big(\frac{b}{2a}\big)^2$ to both sides.

$$x^2+\frac{b}{a}x+\bigg(\frac{b}{2a}\bigg)^2 = -\frac{c}{a}+\frac{b^2}{4a^2}$$

$$\bigg(x+\frac{b}{2a}\bigg)^2 = \frac{b^2-4ac}{4a^2}$$

After which you can take the square root of both sides and solve for $x$. Can you use this general plan to solve the equation you’ve given?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.